Modification of Profitability Measures with Comprehensive Income and Reclassification of Other Comprehensive Income as a Mediation of Effects Asset Utilization on Firm Value - Kusuma, Marhaendra (Jurnal Keuangan dan Perbankan, 2021)
This study modifies financial performance measures by developing a comprehensive income-based measure as the impact of applying fair value accounting and the concept of all-inclusive income, which has an effect on changing the income statement format, and testing its mediating role on the effect of asset utilization on firm value, data from 504 companies on the IDX period 2016 – 2020. The results show that financial performance based on comprehensive income mediates asset utilization on firm value if it only contains net income and other comprehensive income for the group to be reclassified. The net income version of ROA ROE is suitable for evaluating the performance of operating activities, while the comprehensive income version is suitable for evaluating the overall asset utilization performance from the results of revenues that have been realized and have not been realized. Novelty or originality: (1) developing comprehensive profit-based profitability and (2) mediating comprehensive profitability on the effect of asset utilization on firm value.JEL: E64, G32